Toward the prediction of pore volumes and freeze-thaw performance of concrete using thermodynamic modelling. (October 2019) - Bharadwaj, Keshav; Glosser, Deborah; Moradllo, Mehdi Khanzadeh; Isgor, O. Burkan; Weiss, W. Jason
Abstract: Many properties of concrete are related to its pore volume and pore structure. This paper describes an approach to predict gel and capillary pore volumes and other hardened properties of pastes using the pore partitioning model, and scaling these calculated properties to concrete by including entrained and entrapped air and aggregates. This paper focuses on illustrating how parameters that can be used for determining the freeze-thaw performance can be computed using a critical saturation model. Specifically, the degree of saturation and formation factor of the concrete are predicted when the matrix pores are saturated. Based on the model simulations, the secondary rate of sorption can be estimated using the formation factor to predict the potential for reaching a critical degree of saturation which is a measure of concrete's resistance to freeze-thaw damage. This approach allows for the evaluation of the performance of concrete mixtures with a wide variety of binder compositions and mixture proportions. The model predicts the saturated formation factor with a maximum error of 13% and the matrix saturation with a maximum error of 7%. The model can also be used to provide insight into the amount of entrained air needed for a given replacement and reactivity of binder.